Continuous identification of the tea shoot tip and accurate positioning of picking points for a harvesting from standard plantations - Luo, Kun; Zhang, Xuechen; Cao, Chengmao; Wu, Zhengmin; Qin, Kuan; Wang, Chuan; Li, Weiqing; Chen, Le; Chen, Wei (Frontiers in Plant Science, 2023)
To address the current problems of large positioning error, low picking efficiency, and high cost of tea-shoot picking, a continuous and precise harvesting scheme for tea shoots based on a two-dimensional perspective is designed in this study. A high-speed harvesting method for tea shoots in a standardized tea plantation assembly line type was proposed. First, a two-dimensional view recognition model of tea shoot tips in a multi-disturbance environment was constructed, and accurate picking-point coordinates were determined by combining a skeleton algorithm and curve growth. To avoid the losses of recognition accuracy caused by the mistaken clamping of blades and vibrations during harvester operations, accurate control of the harvester was realized by combining path planning and the S-curve speed control function. The recognition accuracy for the verification set of the recognition model was 99.9%, and the mean average precision (0.5:0.95) value was 0.97. The test results show that the error between the actual picking point position and the position determined by the model was within ± 3 mm, and the picking success rate was 83.6%. Therefore, we can realize fast and accurate picking of tea shoots and lay the foundation for continuous tea picking in the future by simplifying the identification and picking process.